Drug utilization pattern of antimicrobials in intensive care unit of a tertiary care teaching hospital - Satapathy, Saswat; Sahu, Yajnesh P.; Panigrahi, Ashok K.; Rath, Bhabagrahi; Patra, Ananta N. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The intensive care unit is a setting where the multiple medications are prescribed to patients. Antimicrobials are heavily prescribed in the ICUs, which in turn enhance the risk of antimicrobial resistance, increase the side effects and increases the cost of treatment. Drug utilization study is a component of medical auditing that aims to monitor and evaluate the drug prescription patterns and to suggest necessary modifications in the prescribing practices to achieve rational therapeutic practice. Methods: A cross-sectional study was conducted in which data of patients admitted to ICU during the period from June 2019 to August 2019 was collected from the Medical Record Section of the hospital. Drug utilization pattern of antimicrobials in ICU was analyzed. Results: Out of 90 patients, 60 were males and 30 were females. The average duration of stay in ICU was 7.53 days. The most common antibiotic prescribed was ceftriaxone followed by piperacillin and tazobactam with DDD/100 bed days of 24.2 and 17.3 respectively. Conclusions: In this study, the results appeared to be similar to those reported in previous studies. However, prescription protocols need to be addressed to guide appropriate use of antimicrobials in the ICU setting. Therefore, it is necessary to conduct drug utilization research to understand the drug consumption and for implementation of protocols to improve the quality of healthcare.